The Role of Education in Enhancing Women’s Skills and Opportunities for Inclusive Sustainable Economic Development in Tangerang City - Etty Herijawati; Rina Aprilyanti; Selfiyan Selfiyan; Lidya Lunardi (eCo-Fin, 2026)
Education plays a pivotal role in enhancing the quality of women’s human resources, which are crucial for driving inclusive economic development; however, many Indonesian women still face barriers in accessing education that aligns with labor market needs. This work focuses on exploring the effects of social support, education level, and education-labor market relevance on women’s human resource quality and empowerment in Tangerang City, providing insights for gender-responsive educational policies. Using a quantitative descriptive-explanatory design and the PLS-SEM approach, data were collected from 155 educated women working across formal and informal sectors. The results show that social support, education level, and educational relevance significantly influence both women’s empowerment and human resource quality, with empowerment serving as a strong mediating variable (R² = 0.864). By expanding women’s access to education and empowering interventions, and by ensuring assistance from familial, community, and governmental actors, the development of high-quality female human resources can be accelerated, leading to more resilient and sustainable economic outcomes within local regions.